The myth of standardized workflow in primary care. (2nd September 2015) - Holman, G Talley; Beasley, John W; Karsh, Ben-Tzion; Stone, Jamie A; Smith, Paul D; Wetterneck, Tosha B
Abstract: Objective Primary care efficiency and quality are essential for the nation's health. The demands on primary care physicians (PCPs) are increasing as healthcare becomes more complex. A more complete understanding of PCP workflow variation is needed to guide future healthcare redesigns. Methods This analysis evaluates workflow variation in terms of the sequence of tasks performed during patient visits. Two patient visits from 10 PCPs from 10 different United States Midwestern primary care clinics were analyzed to determine physician workflow. Tasks and the progressive sequence of those tasks were observed, documented, and coded by task category using a PCP task list. Variations in the sequence and prevalence of tasks at each stage of the primary care visit were assessed considering the physician, the patient, the visit's progression, and the presence of an electronic health record (EHR) at the clinic. Results PCP workflow during patient visits varies significantly, even for an individual physician, with no single or even common workflow pattern being present. The prevalence of specific tasks shifts significantly as primary care visits progress to their conclusion but, notably, PCPs collect patient information throughout the visit. Discussion PCP workflows were unpredictable during face-to-face patient visits. Workflow emerges as the result of a "dance" between physician and patient as their separate agendas are addressed, a side effect of patient-centered practice. Conclusions Future healthcare redesigns should support a wide variety of task sequences to deliver high-quality primary care. The development of tools such as electronic health records must be based on the realities of primary care visits if they are to successfully support a PCP's mental and physical work, resulting in effective, safe, and efficient primary care.